2013
DOI: 10.1111/bjh.12364
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in myeloid malignancies

Abstract: SummaryMicroRNAs (miRNAs) are key to the pathogenesis of human malignancies and increasingly recognized as potential biomarkers and therapeutic targets. Haematological malignancies, being the earliest human malignancies linked to aberrant miRNA expression, have consistently underpinned our understanding of the role that miRNAs play in cancer development. Here, we review the expanding roles attributed to miRNAs in the pathogenesis of different types of myeloid malignancies and highlight key findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 148 publications
0
35
0
Order By: Relevance
“…A high expression of MIR155 and of MIR3151 (Eisfeld et al, 2012) constitutes an independent adverse prognostic factor in CN-AML. Differential expression of a plethora of miRNAs are associated with different cytogenetically or molecular defined subsets of AML, however without proven prognostic significance (Gordon et al, 2013).…”
Section: Micro-rnasmentioning
confidence: 99%
“…A high expression of MIR155 and of MIR3151 (Eisfeld et al, 2012) constitutes an independent adverse prognostic factor in CN-AML. Differential expression of a plethora of miRNAs are associated with different cytogenetically or molecular defined subsets of AML, however without proven prognostic significance (Gordon et al, 2013).…”
Section: Micro-rnasmentioning
confidence: 99%
“…7,8 The importance of miRNAs is further supported by reports of deregulated expression of several miRNAs in hematologic malignancies. [9][10][11] However, functional analysis of miRNA in human as opposed to murine hematopoiesis has been challenging and is less well described.…”
Section: Introductionmentioning
confidence: 99%
“…Gordon et al found hsa-miR-10a, hsa-miR-17/92, hsa-miR-150, hsa-miR-203 and hsa-miR-328 to be the most commonly deregulated miRNAs in CML (14). A miRNA may function as a tumour suppressor or an oncogene (15).…”
Section: Introductionmentioning
confidence: 99%